Designing a Green Chemistry Virtual Laboratory with Project-Based Learning to Improve Acid-Base Titration Outcomes - Mutiara Ardi; Manihar Situmorang; Nurul Aliyyah; Emitur Malau (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study developed a Green Chemistry-oriented virtual laboratory integrated with Project-Based Learning (PjBL) for acid-base titration and evaluated its impact on students' learning outcomes and critical thinking skills. The virtual laboratory was designed using the ADDIE model and implemented as a 2D Canva-based application accessible via laptops and smartphones. The study involved 35 experimental and 36 control group students. Validation by three experts resulted in a media feasibility score of 3.30 ± 0.15. The experimental group achieved an average post-test score of 83.31 ± 5.56, significantly higher than the control group's score of 72.36 ± 4.43. Critical thinking skills also enhanced, with an average score of 88.29 ± 4.82. These findings indicate that the Green Chemistry virtual laboratory significantly improves students' learning outcomes and critical thinking skills.